Emotional difficulties in diabetes mellitus. Issue 4 (April 1986) - Close, H; Davies, A G; Price, D A; Goodyer, I M
Abstract : Sixty children and adolescents with diabetes aged between 9 and 18 years were investigated for emotional difficulties in association with their diabetic control. Seventeen (28%) had appreciable emotional or behavioural difficulties according to parental report, and seven (12%) considered themselves 'possibly depressed'. These latter patients had a mean glycosylated haemoglobin concentration below 10%, poorer self esteem, and a greater external locus of control. Three were considered not to have pronounced emotional difficulties according to parental report.